2000
DOI: 10.1097/00005344-200012000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vasomotor Dysfunction in the Cardiac Allograft: Impact of Different Immunosuppressive Regimens

Abstract: Immunosuppression may have an important impact on early graft coronary endothelial injury. We investigated functional and morphologic coronary alterations, myocardial expression, and cardiac release of possible mediators of allograft vasculopathy within 6 months after cardiac transplantation with respect to different immunosuppressive regimens. Epicardial and microvascular endothelium-dependent and endothelium-independent vasomotor function and epicardial intimal thickening were measured in 8 transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…99 In further support, eNOS immunoreactivity is gradually lost after human heart transplantation, 100 and reduced myocardial eNOS gene expression is associated with coronary endothelial dysfunction. 101 In summary, endothelial dysfunction is an early feature of vascular disease that contributes to the pathogenesis of both atherosclerosis and AV.…”
Section: Role Of Endothelium In Cav and Atherosclerosismentioning
confidence: 99%
“…99 In further support, eNOS immunoreactivity is gradually lost after human heart transplantation, 100 and reduced myocardial eNOS gene expression is associated with coronary endothelial dysfunction. 101 In summary, endothelial dysfunction is an early feature of vascular disease that contributes to the pathogenesis of both atherosclerosis and AV.…”
Section: Role Of Endothelium In Cav and Atherosclerosismentioning
confidence: 99%
“…8,9 There are limited data regarding whether different immunosuppressive regimens after heart transplantation may have a significant impact on progression of CAV. 10 It has been shown that the calcineurin inhibitors cyclosporine A (CsA) and tacrolimus (FK506), which cannot prevent CAV, 5,11 can induce endothelial dysfunction and hypertension, 12,13 which has been explained by an increase in vascular reactive oxygen species (ROS) formation. 14, 15 In contrast to this, the inhibitor of inosine monophosphate dehydrogenase (IMPDH), mycophenolate mofetil, or its active metabolite, mycophenolate acid (MPA), have been associated with positive effects on atherosclerosis or hypertension in animal models.…”
mentioning
confidence: 99%
“…In fact, reversible vasospasm was observed in several CNI-treated patients in the present study (data not shown). Proposed mechanisms by which these drugs cause coronary vasospasm include inhibition of expression of the gene encoding endothelial nitric oxide synthetase (eNOS) and activation of the endothelin (ET) gene (Weis et al 2000). In support of this hypothesis, several groups have demonstrated that administration of CNIs significantly increases concentrations of ET, a potent vasoconstrictive peptide, in plasma from organ-transplant recipients (Haug et al 1995;Slowinski et al 2002).…”
Section: Discussionmentioning
confidence: 99%